Experimental and ANN-based prediction of the mechanical properties of fly ash geopolymer concrete - Swapnil D. Kurhade; Sachin B. Kandekar; Manoj P. Wagh; Deepak A. Vidhate; Vikas D. Gholap; Subhash V. Patankar (Innovative Infrastructure Solutions, 2026)

Genome-Wide Identification, Characterization, and Expression Profiling of GA20-Oxidase Family Genes in Pigeon Pea (Cajanus Cajan L.) - Ishwar Baban Jadhav; Venkat Raman K.; Krishnayan Paul; Mahi Baaniya; Rupam Sarkar; Suparna Das; Subhash A.; Anjali Sharma; Joshitha Vijayan; Rama Prashat G.; Rohini Sreevathsa; Debasis Pattanayak (Journal of Plant Growth Regulation, 2026)

Comparative 28-day mouse study of topically applied aryl hydrocarbon receptor ligands: microbiota-derived indoles, therapeutic tapinarof, pollutants 2,3,7,8-tetrachlorodibenzo-p-dioxin and diesel exhaust particles - Subhash Solanki; Syeda Mashnia Tasnim; Lauren L. Thompson; Madhusudhan Alle; Brandon Ward; Andrzej T. Slominski; Zorica Janjetovic; Teresa Jozwicka; Patrycja Erdmańska; Deborah Minzaghi; Carrie Hayes Sutter; Elizabeth A. Grice; et al. (Chemico-Biological Interactions, 2026)

Weed Management in Fodder Maize Using Herbicides Under Diverse Agro-Climates of India - R. K. Agrawal; Jeetendra Kumar Soni; S. K. Jha; R. V. Kale; Rajesh Kumar; Birendra Kumar; Usha C. Thomas; Subhash Chand; A. K. Roy; A. K. Jha; V. K. Yadav (International Journal of Plant Production, 2026)

Effect of salinity stress on growth, physio-biochemical and ion homeostasis and activation of antioxidant defense responses in Avena spp. - Shahid Ahmed; Parichita Priyadarshini; I. Indu; Maneet Rana; Gajender Yadav; A. K. Rai; Subhash Chand; Monika Yadav; Mahendra Singh; Rajesh Kumar Singhal (Cereal Research Communications, 2025)

Multimodal landscape of atherosclerotic plaques: A spatial omics approach with mass spectrometry imaging - Robin Joshi; Soon Yew Tang; Ujjalkumar Subhash Das; Daniel J. Boehmler; Antonijo Mrčela; Ronan Lordan; E. James Petersson; Aalim M. Weljie; Garret A. FitzGerald (Analytica Chimica Acta, 2025)

Soil Carbon and Nutrient Cycling Regulated by Fine Roots Distribution and Dynamics in Teak (Tectona grandis L.)-Based Agroforestry System in Semi-Arid Central India - Asha Ram; Shubham Choure; Inder Dev; Naresh Kumar; Deepak Singh; Dhiraj Kumar; Sovan Debnath; S. Suresh Ramanan; Ashutosh Dwivedi; Raju Kumar; Sanjana Maurya; Subhash Babu; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Comparative Study on Key Time Series Models for Exploring the Agricultural Price Volatility in Potato Prices - S. Vishnu Shankar; Ashu Chandel; Rakesh Kumar Gupta; Subhash Sharma; Hukam Chand; A. Aravinthkumar; S. Ananthakrishnan (Potato Research, 2025)

Quantitative Analysis on Expression of Insecticidal Crystal Proteins in Different Plant Parts of BG-II Cotton Hybrids at Various Phenological Stages - Debashis Paul; Rishi Kumar; G. Balasubhramani; Sandeep Bagri; Subhash Chandra; S. Manickam; Satpal Singh; A. H. Prakash; Y. G. Prasad (Agricultural Research, 2025)

The SAP-1 payload: A technology demonstration for space-based microbiology experiments - A. Lokaveer; Vikram Khaire; Thomas Anjana; Maliyekkal Yasir; S. Yogahariharan; Akash Dewangan; Saurabh Kishor Mahajan; Sakshi Aravind Tembhurne; Gunja Subhash Gupta; Devashish Bhalla; Anantha Datta Dhruva; Aloke Kumar; et al. (Advances in Space Research, 2025)

Black rice bioactive with multifunctional health promotional activities: A special reference to wound healing activity with polyhydroxybutyrate composite - Subhash Kumar; Gwanjo Lee; Vishal Kumar; Gajanan A. Bodkhe; Youngsook Oh; Gitima Deka; Pil-Hoon Park; Myunghee Kim (Food Chemistry, 2025)

Tunnel wash water in a cold climate: characteristics, ecotoxicological risk, and effect of sedimentation - Nadine A. Sossalla; Wolfgang Uhl; Hanne Vistnes; Subhash Srikantha Rathnaweera; Eilen Arctander Vik; Thomas Meyn (Environmental Science and Pollution Research, 2025)
The characterization of tunnel wash water (TWW) from 12 Norwegian tunnels showed very high concentrations of total suspended solids (TSS), metals, and polycyclic aromatic hydrocarbons (PAHs). Iron (Fe), aluminum (Al), and manganese (Mn) were mainly particle-associated. They are efficiently removed by sedimentation, while the dissolved concentrations of toxic metals like Cu, Zn, and As did not change. Polycyclic aromatic hydrocarbon (PAH) concentration was higher in the dissolved than in the particulate fraction. Sedimentation treatment reduced the particulate share by about 50%. In contrast to metals, the dissolved fraction decreased by about 90% during sedimentation, most probably due to adsorption to particles that are subsequently removed during the process. The concentration levels of 8 out of 16 PAHs, Cu, Zn, and As resulted in a water quality classification of poor or very poor. Acute toxic effects could be expected after short-term exposition. After sedimentation, this was the case for only two PAHs because more harmful compounds with three to six rings were preferably removed. These may adsorb better to particles than PAHs with two rings. No change was observed for the metals. A closer evaluation of secondary treatments of TWW, including conventional technology and mobile solutions, is therefore recommended. Finally, indications for a seasonal pollution variation have been seen, mainly related to the use of salt as a de-icing agent in road maintenance. Graphical Abstract

Presence of emerging organic contaminants and microbial indicators in surface water and groundwater in urban India - Bentje Brauns; Subhash Chandra; Wayne Civil; Dan J. Lapworth; Alan M. MacDonald; Andrew A. McKenzie; Daniel S. Read; Muddu Sekhar; Andrew C. Singer; Amritha Thankachan; Holly J. Tipper (Environmental Pollution, 2024)

Integrated organic nutrient management: a sustainable approach for cleaner maize (Zea mays L.) production in the Indian Himalayas - Amit Kumar; Raghavendra Singh; Subhash Babu; R. K. Avasthe; Anup Das; Aastika Pandey; B. A. Gudade; Ramgopal Devadas; Saurav Saha; Sanjay Singh Rathore (Organic Agriculture, 2024)

Microbiological acceptance criteria, specifications of herbal drugs and herbal drug preparations in various pharmacopoeias: a global scenario - Ramesh Munukuntla; Akhilesh Tiwari; Ravi Shankar Yadav; A. Jayanthy; Subhash Chandra Verma; Raman Mohan Singh (DARU Journal of Pharmaceutical Sciences, 2024)

The Luna structure, India: A probable impact crater formed by an iron bolide - K.S. Sajinkumar; S. James; G.K. Indu; Saranya R. Chandran; Devika Padmakumar; J. Aswathi; S. Keerthy; M.N. Praveen; N. Sorcar; J.K. Tomson; Anil Chavan; Subhash Bhandari; et al. (Planetary and Space Science, 2024)

Design, Development, and Evaluation of SA-F127:TPGS Polymeric Mixed Micelles for Improved Delivery of Glipizide Drug: In-vitro, Ex-vivo, and In-vivo Investigations - Hemil S. Patel; Bhavin A. Vyas; Subhash Tripathi; Rakesh K. Sharma (AAPS PharmSciTech, 2023)

Climate plays a dominant role over land management in governing soil carbon dynamics in North Western Himalayas - Owais Ali Wani; Vikas Sharma; Shamal S. Kumar; Subhash Babu; K.R. Sharma; Sanjay Singh Rathore; Sudeep Marwaha; Nazir A. Ganai; S.R. Dar; Md Yeasin; Raghavendra Singh; Jaibir Tomar (Journal of Environmental Management, 2023)

Potential of camel rumen derived Bacillus subtilis and Bacillus velezensis strains for application in plant biomass hydrolysis - Shweta Srivastava; Sakina Bombaywala; Subhash J. Jakhesara; Niteen V. Patil; Chaitanya G. Joshi; Hemant J. Purohit; Nishant A. Dafale (Molecular Genetics and Genomics, 2023)

Fatty acids analysis, antioxidant, antimicrobial and biological activity of essential oil of Skimmia laureola Leaves - V. K. Bisht; A. K. Bhandari; L. S. Kandari; T. Negi; Subhash Chandra; Sarla Saklani; Santwana Palai; Bruna Caroline Gonçalves Vasconcelo de Lacerda; Henrique D. M. Coutinho (Vegetos, 2023)

Fibro-adipogenesis in Injured Rotator Cuff Muscle - Ajith K. Subhash; Michael Davies; Andrew Gatto; Jacob M. Bogdanov; Rae Lan; Andrew Jensen; Brian T. Feeley; Frank A. Petrigliano (Current Tissue Microenvironment Reports, 2022)
Purpose of Review Fibro-adipogenic progenitors were first characterized in 2010 and later found to contribute significantly to muscle regeneration and mediate degenerative changes in muscle following injury. These progenitors were also found to have an influence on the rotator cuff muscle’s response to chronic injury which is defined by fibrosis accompanied by massive fatty degeneration. The purpose of this review is to highlight progenitor cells, their contribution to fibro-adipogenesis in rotator cuff tissue, and the factors influencing fibro-adipogenesis in this tissue. Recent Findings Fibro-adipogenic progenitors are a key mediator of the fatty infiltration notably prevalent in rotator cuff injury. Relative to other muscle groups, the rotator cuff has relatively high rates of fibro-adipogenesis following massive chronic rotator cuff tears. This may be linked to the pre-injury density of fibro-adipogenic progenitors in muscle tissue affecting post-injury levels of fibro-adipogenesis. In addition, suprascapular nerve injury in rat models of rotator cuff tears has demonstrated worse, histologic, and biomechanical properties and lower healing rates of rotator cuff repairs. However, fatty infiltration in the rotator cuff following suprascapular nerve compression has been shown to be reversible following release of the nerve compression. Summary The fibro-adipogenic response to acute and chronic injury in rotator cuff tissue is determined by a complex array of factors including progenitor cell influence, transcriptional pathways, chronicity of the injury, anatomic location of injury, microenvironmental influences, and the severity of nerve involvement. Elucidating the complex interactions of these factors will provide potential targets for therapeutic intervention in vivo.

Unraveling the camel rumen microbiome through metaculturomics approach for agriculture waste hydrolytic potential - Shweta Srivastava; Nishant A. Dafale; Subhash J. Jakhesara; Chaitanya G. Joshi; Niteen V. Patil; Hemant J. Purohit (Archives of Microbiology, 2021)

Computationally simple anisotropic lattice covariograms - Dean Koch; Subhash Lele; Mark A. Lewis (Environmental and Ecological Statistics, 2020)

Exploring the eukaryotic diversity in rumen of Indian camel (Camelus dromedarius) using 18S rRNA amplicon sequencing - Priyaranjan Mishra; Nilam J. Tulsani; Subhash J. Jakhesara; Nishant A. Dafale; Niteen V. Patil; Hemant J. Purohit; Prakash G. Koringa; Chaitanya G. Joshi (Archives of Microbiology, 2020)

Fisetin, a plant flavonoid ameliorates doxorubicin-induced cardiotoxicity in experimental rats: the decisive role of caspase-3, COX-II, cTn-I, iNOs and TNF-α - Tao Ma; Amit D. Kandhare; Anwesha A. Mukherjee-Kandhare; Subhash L. Bodhankar (Molecular Biology Reports, 2019)

Attenuation of cocaine seeking in rats via enhancement of infralimbic cortical activity using stable step-function opsins - Victória A. Müller Ewald; Benjamin J. De Corte; Subhash C. Gupta; Katherine V. Lillis; Nandakumar S. Narayanan; John A. Wemmie; Ryan T. LaLumiere (Psychopharmacology, 2019)

Spatiotemporal dynamics and genome‐wide association analysis of desiccation tolerance in Drosophila melanogaster - Subhash Rajpurohit; Eran Gefen; Alan O. Bergland; Dmitri A. Petrov; Allen G. Gibbs; Paul S. Schmidt (Molecular Ecology, 2018)
Water availability is a major environmental challenge to a variety of terrestrial organisms. In insects, desiccation tolerance varies predictably over spatial and temporal scales and is an important physiological determinant of fitness in natural populations. Here, we examine the dynamics of desiccation tolerance in North American populations of Drosophila melanogaster using: (a) natural populations sampled across latitudes and seasons; (b) experimental evolution in field mesocosms over seasonal time; (c) genome‐wide associations to identify SNP s/genes associated with variation for desiccation tolerance; and (d) subsequent analysis of patterns of clinal/seasonal enrichment in existing pooled sequencing data of populations sampled in both North America and Australia. A cline in desiccation tolerance was observed, for which tolerance exhibited a positive association with latitude; tolerance also varied predictably with culture temperature, demonstrating a significant degree of thermal plasticity. Desiccation tolerance evolved rapidly in field mesocosms, although only males showed differences in desiccation tolerance between spring and autumn collections from natural populations. Water loss rates did not vary significantly among latitudinal or seasonal populations; however, changes in metabolic rates during prolonged exposure to dry conditions are consistent with increased tolerance in higher latitude populations. Genome‐wide associations in a panel of inbred lines identified twenty‐five SNP s in twenty‐one loci associated with sex‐averaged desiccation tolerance, but there is no robust signal of spatially varying selection on genes associated with desiccation tolerance. Together, our results suggest that desiccation tolerance is a complex and important fitness component that evolves rapidly and predictably in natural populations.

Analysis of spatial distribution of genetic diversity and validation of Indian foxtail millet core collection - Subhash Chander; K. V. Bhat; Ratna Kumari; Sanjay Sen; A. B. Gaikwad; M. V. C. Gowda; N. Dikshit (Physiology and Molecular Biology of Plants, 2017)

Dose-dependent response of Trichoderma harzianum in improving drought tolerance in rice genotypes - Veena Pandey; Mohammad W. Ansari; Suresh Tula; Sandep Yadav; Ranjan K. Sahoo; Nandini Shukla; Gurdeep Bains; Shail Badal; Subhash Chandra; A. K. Gaur; Atul Kumar; Alok Shukla; et al. (Planta, 2016)

Antagonism of angiotensin 1–7 prevents the therapeutic effects of recombinant human ACE2 - Vaibhav B. Patel; Abhijit Takawale; Tharmarajan Ramprasath; Subhash K. Das; Ratnadeep Basu; Maria B. Grant; David A. Hall; Zamaneh Kassiri; Gavin Y Oudit (Journal of Molecular Medicine, 2015)

Development of a validated UPLC-qTOF-MS Method for the determination of curcuminoids and their pharmacokinetic study in mice - Mahendra K Verma; Ishtiyaq A Najar; Manoj K Tikoo; Gurdarshan Singh; Devinder K Gupta; Rajneesh Anand; Ravi K Khajuria; Subhash C Sharma; Rakesh K Johri (DARU Journal of Pharmaceutical Sciences, 2013)

Reversal of boswellic acid analog BA145 induced caspase dependent apoptosis by PI3K inhibitor LY294002 and MEK inhibitor PD98059 - Anup S. Pathania; Amit Joshi; Suresh Kumar; Santosh K. Guru; Shashi Bhushan; Parduman R. Sharma; Wajid W. Bhat; Ajit K. Saxena; Jaswant Singh; Bhahwal A. Shah; Samar S. Andotra; Subhash C. Taneja; et al. (Apoptosis, 2013)

Pro-apoptotic properties of parthenin analogs: a quantitative structure–activity relationship study - Rukmankesh Mehra; Amit Nargotra; Bhahwal A. Shah; Subhash C. Taneja; Ram A. Vishwakarma; Surrinder Koul (Medicinal Chemistry Research, 2013)

In vitro antioxidant activity and phenolic contents in methanol extracts from medicinal plants - Sanjay Guleria; A. K. Tiku; Gurjinder Singh; Apurva Koul; Sahil Gupta; Subhash Rana (Journal of Plant Biochemistry and Biotechnology, 2013)

Analgesic and anti-inflammatory activity of β-sitosterol isolated from Nyctanthes arbortristis leaves - Sunil A. Nirmal; Subodh C. Pal; Subhash C. Mandal; Anuja N. Patil (Inflammopharmacology, 2012)

Association of 1347 G/A cytochrome P450 4F2 (CYP4F2) gene variant with hypertension and stroke - Anjana Munshi; Vandana Sharma; Subhash Kaul; Amal Al-Hazzani; Ali A. Alshatwi; Gowhar Shafi; Rajeshwar Koppula; Sai Babu Mallemoggala; A. Jyothy (Molecular Biology Reports, 2012)

A new species of portunid crab of the genus Charybdis (De Haan, 1833) (Crustacea: Decapoda: Brachyura) from Goa, India - Vinay P. Padate; Chandrashekher U. Rivonker; A. Chandrashekar Anil; Subhash S. Sawant; Venkat Krishnamurthy (Marine Biology Research, 2010)

Structure-Activity Studies on Therapeutic Potential of Thymoquinone Analogs in Pancreatic Cancer - Sanjeev Banerjee; Asfar S. Azmi; Subhash Padhye; Marjit W. Singh; Jubaraj B. Baruah; Philip A. Philip; Fazlul H. Sarkar; Ramzi M. Mohammad (Pharmaceutical Research, 2010)

Synthesis of some novel 2-substituted benzoxazoles as anticancer, antifungal, and antimicrobial agents - P. K. Jauhari; A. Bhavani; Subhash Varalwar; Kiran Singhal; Prem Raj (Medicinal Chemistry Research, 2008)

Oxygenated chalcones and bischalcones as a new class of inhibitors of DNA topoisomerase II of malarial parasites - Shalini Srivastava; Shweta Joshi; Alok R. Singh; Sarika Yadav; A. S. Saxena; V. J. Ram; Subhash Chandra; J. K. Saxena (Medicinal Chemistry Research, 2008)

Using form analysis techniques to improve photogrammetric mass‐estimation methods - Kelly M. Proffitt; Robert A. Garrott; Jay J. Rotella; Subhash Lele (Marine Mammal Science, 2008)
Numerical characterization of animal body forms using elliptical Fourier decomposition may be a useful analytic technique in a variety of marine mammal investigations. Using data collected from the Weddell seal ( Leptonychotes weddellii ), we describe the method of body form characterization using elliptical Fourier analysis and demonstrated usefulness of the technique in photogrammetric mass‐estimation modeling. We compared photogrammetric mass‐estimation models developed from (1) standard morphometric measurement covariates, (2) elliptical Fourier coefficient covariates, and (3) a combination of morphometric and Fourier coefficient covariates and found that mass‐estimation models employing a combination of morphometric measurements and Fourier coefficients outperformed models containing only one covariate type. Inclusion of Fourier coefficients in photogrammetric mass‐estimation models employing standard morphometric measurements reduced the width of the prediction interval by 24.4%. Increased precision of photogrammetric mass‐estimation models employing Fourier coefficients as model covariates may expand the range of ecological questions that can be addressed with estimated mass measurements.

Immunological evaluation of urinary trypsin inhibitors in blood and urine: Role of N- & O-linked glycoproteins - Michael J. Pugia; Saeed A. Jortani; Manju Basu; Ronald Sommer; Hai-Hang Kuo; Solomon Murphy; Doug Williamson; James Vranish; Patrick J. Boyle; Danny Budzinski; Roland Valdes; Subhash C. Basu (Glycoconjugate Journal, 2007)

NMI-1182, a gastro-protective cyclo-oxygenase-inhibiting nitric oxide donor - James L. Ellis; Michael E. Augustyniak; Edward D. Cochran; Richard A. Earl; David S. Garvey; Laura J. Gordon; David R. Janero; Subhash P. Khanapure; L. Gordon Letts; Terry L. Melim; Madhavi G. Murty; David J. Schwalb; et al. (Inflammopharmacology, 2005)

Nano-biosensor development for bacterial detection during human kidney infection: Use of glycoconjugate-specific antibody-bound gold NanoWire arrays (GNWA) - Manju Basu; Sara Seggerson; Joshua Henshaw; Juan Jiang; Rocio del A Cordona; Clare Lefave; Patrick J. Boyle; Albert Miller; Michael Pugia; Subhash Basu (Glycoconjugate Journal, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Ultrastructure of potato tubers infected with potato virus X - N. I. Mondy; Subhash Chandra; M. A. Cukierski (American Journal of Potato Research, 1980)